(untitled) (Research, Society and Development, 2025)
Chronic and difficult-to-heal wounds represent a relevant challenge in healthcare, demanding effective, accessible, and safe therapeutic options. Aloe vera stands out for its anti-inflammatory, healing, analgesic, and regenerative properties. This study aimed to identify the main scientific evidence on the efficacy of Aloe vera use in wound treatment. This is a narrative literature review with searches conducted in Scielo, Lilacs, and Medline databases. After applying inclusion and exclusion criteria, 13 studies were selected that address the topical use of the plant in surgical wounds, burns, chronic ulcers, and in vitro models. The results confirmed the superiority of Aloe vera over silver sulfadiazine, demonstrating superior efficacy with lower toxicity. In surgical wounds, there is evidence of benefits in various postoperative procedures. Regarding chronic wounds, the results showed divergences. The study highlights that Aloe vera accelerates epithelialization, reduces inflammation and pain, stimulates cell proliferation, and presents low incidence of adverse effects in acute wounds. Its use represents a viable complementary therapy for surgical wounds and burns, while its application in chronic wounds requires additional studies to clarify existing controversies.